Pendulum test in chronic hemiplegic stroke population: additional ambulatory information beyond spasticity - Yin-Kai Dean Huang (Nature Portfolio, 2021)
Abstract Spasticity measured by manual tests, such as modified Ashworth scale (MAS), may not sufficiently reflect mobility function in stroke survivors. This study aims to identify additional ambulatory information provided by the pendulum test. Clinical assessments including Brünnstrom recovery stage, manual muscle test, MAS, Tinetti test (TT), Timed up and go test, 10-m walk test (10-MWT), and Barthel index were applied to 40 ambulant chronic stroke patients. The pendular parameters, first swing excursion (FSE) and relaxation index (RI), were extracted by an electrogoniometer. The correlations among these variables were analyzed by the Spearman and Pearson partial correlation tests. After controlling the factor of motor recovery (Brünnstrom recovery stage), the MAS of paretic knee extensor was negatively correlated with the gait score of TT (r =  − 0.355, p = 0.027), while the FSE revealed positive correlations to the balance score of TT (r = 0.378, p = 0.018). RI were associated with the comfortable speed of 10-MWT (r = 0.367, p = 0.022). These results suggest a decrease of knee extensor spasticity links to a better gait and balance in chronic stroke patients. The pendular parameters can provide additional ambulatory information, as complementary to the MAS. The pendulum test can be a potential tool for patient selection and outcome assessment after spasticity treatments in chronic stroke population.